Trajectories of child mental health, physical activity and screen-time during the COVID-19 pandemic considering different family situations: results from a longitudinal birth cohort - Deborah Kurz; Stefanie Braig; Jon Genuneit; Dietrich Rothenbacher (BMC, 2023)
Abstract Background Many authors have described a significant mental health burden on children and adolescents during the COVID-19 pandemic, possibly moderated by social disparities. This analysis explores whether pre-pandemic family circumstances might be related to different aspects of child health during the pandemic. Methods We analyzed trajectories of health-related outcomes in children aged 5 to 9 years (T7 to T11) using the Ulm SPATZ Health study, a population based birth cohort study (baseline 04/2012-05/2013) conducted in the South of Germany. Outcomes were children's mental health, quality of life, and lifestyle, such as screen time and physical activity. We conducted descriptive statistics of maternal and child characteristics before and throughout the pandemic. We defined three different groups of pre-pandemic family situations and used adjusted mixed models to estimate differences in means associated with the time during the pandemic vs. before the pandemic in (a) all children and in (b) children belonging to specific pre-pandemic family situations. Results We analyzed data from n = 588 children from whom at least one questionnaire was completed between T7 and T11. When not considering the pre-pandemic family situation, adjusted mixed models showed statistically significant lower mean scores of health-related quality of life among girls during vs. before the COVID-19 pandemic (difference in means (b): − 3.9 (95% confidence interval (CI): − 6.4, − 1.4). There were no substantial differences in mental health, screen time, or physical activity in boys or girls. When considering pre-pandemic family situations, boys with mothers having symptoms of depression or anxiety showed a substantial loss of health-related quality of life on the subscale of friends (b: − 10.5 (95% CI: − 19.7, − 1.4)). Among girls in this group, 60% of the 15 assessed outcomes were negatively associated with a remarkable loss in health-related quality of life (e.g., KINDL-physical well-being difference in means: − 12.2 (95% CI: − 18.9, − 5.4)). Furthermore, a substantial increase in screen time was found (+ 2.9 h (95% CI: 0.3, 5.6)). Conclusion Our results suggest that the health (and behavior) of primary school-aged children is possibly impacted by the COVID-19 pandemic, with adverse consequences differing by gender and very likely by the pre-pandemic family situation. Especially in girls having a mother with depression or anxiety symptoms, the adverse consequences of the pandemic on mental health seem to be aggregated. Boys showed fewer adverse trajectories, and it needs to be further assessed which factors exactly are behind the (socio-economic) factors, such as maternal working habits and limited living space, when analyzing the effect of the pandemic on children's health.